Longitudinality in childcare provided through Family Health Strategy - Elenice Maria Cecchetti Vaz; Rafaella Karolina Bezerra Pedrosa Magalhães; Beatriz Rosana Gonçalves de Oliveira Toso; Altamira Pereira da Silva Reichert; Neusa Collet
Objective: to evaluate the longitudinality attribute in childcare provided through the Family Health Strategy. Method: quantitative survey performed with 344 caregivers of children below 10 years old, registered in the family health strategy of Distrito Sanitario III in João Pessoa, Paraiba. Data were collected from July to December, 2012, from the Brazil PCATool child version form and analyzed using descriptive statistics. Results: among the aspects evaluated, it is highlighted that 89.5% of caregivers said they were consulted by the same professionals, and 81.9% felt good talking to the professional. The average score for the longitudinality component was satisfactory, with a 6.6 value. Conclusion: the health facilities assessed are guided towards the longitudinality attribute, however, the target mean score was exactly the cutoff value, implying the need for a thoughtful look at the improvement of the attribute in the care of children under ten years.